A REVIEW OF INNOVATIVE WORK BEHAVIOR AND INNOVATIVE CULTURE TOWARDS COMPANY PERFORMANCE - Noor Shakina binti Rabul Jalil; Nor Adriana Sofia binti Nornasaruddin; Nor Shuhada binti Saharunizam; Nur Azarina binti Ismail; Siti Nuraisyah binti Abdul Hamid; Aini Qamariah binti Mohd Yusof (International Journal of Accounting, Finance and Business, 2022)
Innovative Work Behavior is a motivation for employees who have high confidencein areas related to the tendency to be innovative in their work behavior in order to develop asuccessful company. Great innovation necessitates questioning assumptions, focusing onhuman problems rather than answers, experimenting and collaborating, changing gears andsprinting when necessary, and, most all, embracing positive ambiguity. However, a firm'sinnovative performance is influenced not just by internal resources, but also by knowledge andskills created outside the organization in collaboration with others. A key factor of performanceinnovation is the innovation of approach to creating value for customers to remain competitiveand have a strategy. This review study is intended to identify the importance of innovative workbehavior towards innovative performance and innovative culture. Innovation is also carried ina much contextual literature and has major themes on aspects of usefulness, novelty, creativity.As an action for seek, develop, and implement ideas to solve and help the company achieve thegoal of finding a new idea and provide support to the company to support the idea. Innovationresearch lacks a profound empirical study to date which analyzes the relationship betweenorganizational culture and innovative performance on the firm level.